Echocardiography (Springer International Publishing, 2018)
This updated textbook provides an essential evidence-based approach to echocardiography and includes practical case-based instruction illustrating a wide variety of clinical scenarios in which echocardiography is a vital diagnostic option for physicians. It reflects how echocardiography has evolved into a complex multimodality method for evaluating and quantifying cardiovascular lesions, and explains the use of hemodynamic assessment of the heart using echocardiography, transesophageal and three-dimensional echocardiography, deformation imaging and assessment of myocardial perfusion, which have added a new dimension to real-time noninvasive evaluation of patients. Echocardiography highlights the clinical utility of these evolving modalities that are now crucial to the renaissance of echocardiography, and it provides a thorough clinical review of this most revealing and adaptable methods of imaging a patient. The Editors and their world-class group of contributors have created an essential reference for those in training or who already use echocardiography in their practice. .